2022
DOI: 10.3390/en15197260
|View full text |Cite
|
Sign up to set email alerts
|

The Environmental Protection and Effective Energy Consumption in the Light of the EFQM Model 2020—Case Study

Abstract: This research uses an inductive inference approach supported by a literature study and deductive reasoning supported by a case study method. This article is based on a comprehensive literature review which was a foundation for preparation a planned research in organizations implementing the EFQM 2020 Model in order to build a strategy for sustainable development and energy conservation. EFQM is an abbreviation for the name of the European Foundation for Quality Management, a member organization associating ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…However, the cooperation between organizations in such a system brings more positive than adverse effects. Companies specializing in a particular field are less likely to be re-branded, whereas newly established start-ups have the opportunity to fully adapt to the market and a given demand for specific services or products [13].…”
Section: Slr Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the cooperation between organizations in such a system brings more positive than adverse effects. Companies specializing in a particular field are less likely to be re-branded, whereas newly established start-ups have the opportunity to fully adapt to the market and a given demand for specific services or products [13].…”
Section: Slr Resultsmentioning
confidence: 99%
“…New technologies and innovations [1,2], related to the Industry 4.0 idea in the energy sector [3,4], are genuinely powering the digital economy [5,6]. Industry 4.0 is a concept related to the use of automation [7], data processing [8], and data exchange [9], employed especially in practice in car charging stations, its infrastructure [10,11], and energy distribution networks [12,13]. The electromobility is developed through the Industry 4.0 features [14,15], which can be measured by the growing number of electric cars or electric vehicles (EVs) [16,17] and charging stations [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Yu, Khan and Umar (2022) concluded that I4.0 has a positive impact on the implementation of a circular economy (CE), and, in its turn, a CE has a positive impact on operational and economic performance. Also, as reported by Martusewicz, Szewczyk and Wierzbic (2022), the concept of CE is mentioned in the EFQM model in criteria 5.5 and 6. Turisová et al (2020) used this model version to analyse the readiness of companies for I4.0 in a specified area.…”
Section: Excellence Models and Corporate Sustainabilitymentioning
confidence: 95%
“…In turn, the newest EFQM model version is highly oriented towards promoting sustainability (Muhammad Din et al, 2021;Val, Regaliza and Maraña, 2020). Martusewicz, Szewczyk and Wierzbic (2022) concluded that the model in analysis is a great tool to "create, implement and monitor strategies" regarding environmental practices. Politis and Grigoroudis (2022) 3.4, 3.5, 4.3, 5.1, 5.2, 5.3, 5.4, 5.5, 6, and 7, reaffirming the urge to innovate, promote creativity, develop a "disruptive thinking", and promote the use of technology (Fonseca, 2022;Martusewicz, Szewczyk and Wierzbic, 2022;Politis and Grigoroudis, 2022).…”
Section: Excellence Models and Corporate Sustainabilitymentioning
confidence: 99%
“…This involves not only the expansion of the energy infrastructure but also the provision of adequate power. Unfortunately, RES are characterized by instability of energy production and varying efficiency [141], e.g., due to geographical location [142]. Therefore, protection against the loss of so-called blackouts from RES is being sought through energy storage and the creation of closed energy circuits.…”
mentioning
confidence: 99%